Spontaneous bacterial empyema in a non cirrhotic end stage renal disease patient with immunosuppression. (2016) - Lourdusamy, Dennis; Munshi, Lubna B.; Eltawansy, Sherif Ali
Abstract: Spontaneous Bacterial Empyema (SBEM) denotes infection of the pleural fluid in the absence of pneumonia. Almost all cases of SBEM in literature are described in a background of ascites secondary to cirrhosis. Contiguous spread of the infected ascitic fluid through defects in the diaphragm is the most likely mechanism of SBEM. Most of these cases are transudative in nature and are managed with antibiotics. Literature on SBEM in the absence of cirrhosis or ascites is very limited so far. We describe a 59 year old female with ESRD status post renal transplant, on chronic immunosuppression for renal allograft rejection who was admitted with pleuritic chest pain that turned to be secondary to right sided pleural effusion. Further evaluation revealed Escherichia coli in both the blood and pleural fluid. There was no clinical or imaging evidence of pneumonia as well as cirrhosis or ascites. She was managed as a case of SBEM requiring drainage by chest tube. Management of SBEM in non-cirrhotic individuals usually requires drainage with chest tube as against patients with liver cirrhosis with hepatic hydro-thorax in whom chest tube drainage is contraindicated for risk of massive protein and electrolyte depletion and dehydration.